Thoughts of Self‐Harm and Help‐Seeking Behavior among Youth in the Community. Issue 3 (5th February 2013) - Goodwin, Renee D.; Mocarski, Michelle; Marusic, Andrej; Beautrais, Annette
<x xml:space="preserve">Abstract</x> The association between thoughts of self‐harm and help‐seeking among youth with symptoms of depression was examined. Data were drawn from the Health Behavior of School‐aged Children Study (n = 15, 686), a nationally representative sample of youth in the United States. Analyses focused on comparing help‐seeking behaviors among youth with and without thoughts of deliberate self‐harm (DSH) when depressed. Depressed youth with thoughts of DSH exhibited different patterns of help‐seeking than those without. Both groups most frequently sought help from friends and parents. However, adolescents with thoughts of DSH were statistically more likely than youth without to seek help from friends (DSH: 69.9%; no DSH: 57.8%; AOR = 1.46), but less likely to seek help from parents (DSH: 53.7%; no DSH: 73.1%; AOR = 0.47). Youth with DSH were more likely to seek help from school officials (AOR = 1.05), health professionals (AOR: 1.83), or a counselor (AOR = 1.93) compared with those without thoughts of DSH who were more likely to seek help from a sibling (AOR: 0.77) or other relatives (AOR: 0.78). Results may help inform programs to improve identification of youth at risk of self‐harm in community and school settings.